Subcutaneous Recurrences of Thyroid Cancer After Conventional Transcervical Thyroidectomy: A Case Report - Dong, Xubin; Lv, Shihui; Zhang, Xiaohua; Li, Quan (Frontiers in Surgery, 2020)
Metastatic subcutaneous implantation of the follicular variant of papillary thyroid cancer is very rare. We present a 62-year-old woman with a history of follicular variant of papillary thyroid cancer, who developed multiple asymptomatic subcutaneous nodules, after five years of initial thyroidectomy. Eventually, the subcutaneous nodules were diagnosed as tumor recurrence and completely excised. She has reportedly lived for more than one year, without signs of disease progression or recurrence. This case emphasizes the need for surgeons to take into account the tumor-free concept during the operation, and to a great extent prevent the occurrence of implantation recurrence.